AN ANALYSIS OF IDEATIONAL MEANING IN THE EVERGREEN SONGS AND ITS CONTRIBUTION TO THE TEACHING NARRATIVE TEXTS - Erni Yuhriyah (Universitas PGRI Semarang, 2014)
This final project is aimed at analyzing Ideational meaning in the Evergreen Songs. The objectives of the study are (1) to identify the ideational meaning realized in Evergreen songs, (2) to find out the processes that appear in Evergreen Songs, (3) to find out the clause types that appear in Evergreen Songs, (4) to know the dominant process type found in Evergreen Songs, (5) to find out the result of research in teaching narrative texts.In conducting the research, descriptive qualitative is used in this study because it just collects the data and writes the conclusion based on the analysis of the data. The object of the study is Evergreen Songs Lyrics. The song lyrics have been taken as a sample. Unit of analysis of this study is clause. The researcher is the instrument in this qualitative study. To collect the data, documentation method is applied. The techniques to analyze the data are: determining the song lyrics, identifying the processes based on ideational meaning analysis including participant, process, and circumstance, grouping the types of process from each clause to get dominant process of the song lyrics, and reviewing and discussing the result of the result of the research findings.The research of this study is presented based on the research findings. The ideational meaning of Evergreen songs is realized by participant, process, and circumstance. The dominant process employed in this song lyrics is material process (33,7%). The participants, which are mostly used, are actor and goal. And circumstance of time is dominantly used in the texts. Finally, some suggestions are (1) the result of this research can be used by the English learners to enhance their understanding about metafunction especially ideational meaning, (2) the research can be used by lectures as additional reference in teaching narrative texts and Systemic Functional Grammar, (3) the result of this research can be used by new researcher for understanding the messages are organized in ideational meaning analyzes deeply